Cowboy & Octopus - Scieszka, Jon; Smith, Lane (New York : Viking, 2007)
After Octopus helps Cowboy fix a broken seesaw, the two very different creatures become firm friends.
Keywords: Friendship -- Fiction; Cowhands -- Fiction; Octopuses -- Fiction; Fiction